2018
DOI: 10.3389/fchem.2018.00289
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Binding Interaction of the α,α′,δ,δ′-Tetramethylcucurbit[6]uril With Biogenic Amines in Solution and the Solid State

Abstract: 1H NMR spectroscopy and MALDI-TOF mass spectrometry were utilized to examine the binding interaction of α,α′,δ,δ′-tetramethylcucurbit[6]uril (TMeQ[6]) and six biogenic amines (spermine, spermidine, 2-phenethylamine, tyramine, histamine, and tryptamine). Their 1H NMR spectra both at pD = 7 and pD = 3 revealed that four biogenic amines (spermine, spermidine, 2-phenethylamine, and histamine) can fit in the TMeQ[6] cavity, respectively, and other biogenic amines were located outside of the TMeQ[6] portal. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In particular, cucurbit[ n ]urils (Q[ n ]s) are made up of n glycoluril units connected via 2n methylene bridges (Day et al, 2000; Kim et al, 2000; Cong et al, 2016). These hosts have highly polar carbonyl-fringed portals with hydrophobic cavities that can create remarkably stable complexes with different guest molecules (Kim, 2002; Dsouza et al, 2011; Gao et al, 2017; Liu J. et al, 2017; Murray et al, 2017; Yang et al, 2018). The origination of inclusion complexes frequently improves or interrupts the photo-physical and photo-chemical characteristics of the guest molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, cucurbit[ n ]urils (Q[ n ]s) are made up of n glycoluril units connected via 2n methylene bridges (Day et al, 2000; Kim et al, 2000; Cong et al, 2016). These hosts have highly polar carbonyl-fringed portals with hydrophobic cavities that can create remarkably stable complexes with different guest molecules (Kim, 2002; Dsouza et al, 2011; Gao et al, 2017; Liu J. et al, 2017; Murray et al, 2017; Yang et al, 2018). The origination of inclusion complexes frequently improves or interrupts the photo-physical and photo-chemical characteristics of the guest molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Cucurbit[n]urils (Q[n]s), a relatively new class of macrocyclic compounds composed of a rigid hydrophobic cavity and two identical carbonyl‐laced portals, possess excellent host‐guest inclusion properties and have been widely used as building blocks for rotaxanes and pseudorotaxanes . Among of Q[n]‐based rotaxane/pseudorotaxane systems, most axle molecules have been built from ammonium, pyridinium ions and viologen derivatives . Compared with viologen derivatives, bispyridinium ethylene derivatives have many advantageous including excellent fluorescence properties and light‐controlled reversible E/Z isomerisation, Q[n]‐based rotaxane/pseudorotaxane systems have also been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the bioactivities have been related to their cationic nature, because they can interact with negatively charged macromolecules such as DNA, RNA, and proteins. It has also been shown that they can bind to specific positions or structural motifs in macromolecules via multiple noncovalent interactions, thereby affecting the structure and function of their macromolecular targets. Among the numerous compounds isolated from Sinularia soft corals, spermidine or spermine derivatives are rare. These primarily consist of fatty acid substituted derivatives, and only one compound previously reported from Sinularia contained polyprenylated spermidine or spermine moieties. This compound was named sinulamide, and it was initially assigned structure 1 by the Fusetani group .…”
mentioning
confidence: 99%